2010
DOI: 10.1007/s13213-010-0157-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of bacteriocin production by Lactobacillus acidophilus AA11, a strain isolated from Egyptian cheese

Abstract: The aim of this work was to investigate the effect of growth conditions on the maximum activity of bacteriocin production by Lactobacillus acidophilus AA11. The bacteriocin was produced at maximum activity in M17 broth supplemented with 0.5% lactose (M17L). The maximum growth of Lactobacillus acidophilus AA11 was obtained at 37°C, while the optimal temperature for the bacteriocin production was 30°C. The pH of bacterial culture also affected bacteriocin production. The optimal pH for bacterial growth and bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 47 publications
(53 reference statements)
2
17
0
Order By: Relevance
“…In agreement with our study, Iyapparaj et al (2013), Abo-Amer (2011) and Moreno et al (2003) showed maximum bacteriocin yield by LAB in the presence of lactose as a source of carbon in the production medium. On the other hand, the antagonistic activity of bacteriocin was increased when glucose was added to the medium (Ekhay et al 2013; Todorov 2008).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our study, Iyapparaj et al (2013), Abo-Amer (2011) and Moreno et al (2003) showed maximum bacteriocin yield by LAB in the presence of lactose as a source of carbon in the production medium. On the other hand, the antagonistic activity of bacteriocin was increased when glucose was added to the medium (Ekhay et al 2013; Todorov 2008).…”
Section: Discussionsupporting
confidence: 93%
“…The optimum temperature for growth and bacteriocin production are correlated as observed in lactocin A, 89 94 The optimal temperature for bacteriocin production may not be similar to that of optimal temperature for bacterial growth. 21,30,95,96 There are also reports on maximum bacteriocin production at suboptimal growth temperatures. In the case of amylovorin L471, slow growth at low temperature was suggested to be attributed to the release of more energy for bacteriocin production by L. amylovorus DCE 471.…”
Section: Temperaturementioning
confidence: 99%
“…Also the use of CaCl 2 in the manufacture process of Cheddar cheese might have affected the activity of the bacteriocin. According to Abo‐Amer (2011) and Arakawa et al. (2009), the presence of CaCl 2 in the cultivation broth resulted in a dramatic reduction in bacteriocin production by Lactobacillus acidophilus AA11 and Lactobacillus gasseri LA158, respectively.…”
Section: Resultsmentioning
confidence: 99%